Nanomagnetism and spintronics - Shinjo, Teruya, 1938- (Elsevier, 2009)
Spintronics is a newly developing area in the field of magnetism, where the interplay of magnetism and transport phenomena is studied experimentally and theoretically. This book introduces the recent progresses in the researches relating to spintronics. - From electronics to spintronics. - Electron has not only charge but also spin - Spin current is the key word for future devices. - How peculiar are nanostructured magnetic systems? - What is GMRH: From discovery to applications (in case that GMR got the Nobel prize in 2007).
Keywords: Spintronics.; Nanoelectromechanical systems.; Electromagnetism.; elektronické knihy; electronic books